PENGARUH DEBT EQUITY RATIO, CURRENT RATIO, RETURN ON ASSETS DAN STRUKTUR KEPEMILIKAN INSTITUSIONALTERHADAP RETURN SAHAM PERUSAHAAN PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Meri Daryanti, 13.05.51.0012 (Students Journal of Economic and Management, 2017)
The purpose of this research is to analyze the influence of debt equity ratio, current ratio, return on assets and institutional ownership structure to stock return of property companies listed in Indonesia Stock Exchange year 2013-2015. The population in this study are all property companies listed on the BEI during the period of 2013-2015. Selection of sample by using purposive sampling method obtained by sample as many as 32 companies for 3 years so that the total sample of 96 data observation. Analyzer used is multiple linear regression. The results of the analysis can be concluded that: Debt to equity ratio has a significant positive effect on stock return. Current ratio has no effect on stock return. Return on assets have a significant positive effect on stock return. Institutional ownership has no effect on stock returns. Keywords: debt equity ratio, current ratio, return on assets, institutional ownership structure and stock return